Performance of moving bed biofilm and lamella clarifier hybrid technology to improve hospital wastewater quality - Selamet Jaya Sukmana; Arlini Dyah Radityaningrum; Catur Bagus Priyono (Jurnal Teknosains, 2025)
Surface water pollution caused by the discharge of domestic wastewater, including that from hospitals, is a serious issue that threatens public health and environmental quality. Hospital wastewater typically contains high concentrations of organic matter (COD, BOD), suspended solids (TSS), and pathogenic compounds that may exceed the quality standards set by the Ministry of Environment and Forestry, as outlined in Regulation No. 68 of 2016. This study aims to evaluate the performance of a combination of a Moving Bed Biofilm Reactor (MBBR) using Kaldness K1 media and a Lamella Clarifier in reducing COD, BOD, and TSS levels, as well as stabilizing the effluent pH of hospital wastewater at the laboratory scale. The research employed an experimental approach, utilizing a laboratory wastewater treatment plant design comprising MBBR and Lamella Clarifier units. Wastewater samples were collected by grab sampling from the hospital treatment plant inlet, then diluted to varying concentrations of 20%, 30%, and 50%, and subjected to a 24-hour retention time. The analyzed parameters included COD, BOD, TSS, and pH. The treatment results were statistically analyzed using a paired t-test to assess the significance of concentration reductions before and after treatment. The results indicated that the combination of these two units achieved average reductions of BOD by 56%, COD by 34%, and TSS by 53%, with effluent pH between 7.3 and 7.6, meeting quality standards. Statistical analysis revealed significant differences (p < 0.05) between inlet and outlet conditions, indicating the system's effectiveness. Therefore, the integration of MBBR and Lamella Clarifier is considered a viable solution for efficient, stable, and regulation-compliant hospital wastewater treatment.